GENERIC STRUCTURE POTENTIAL ANALYSIS OF VIETNAMESE PRECEDENTS - Ly, Phan Tuan (VNU Journal of Foreign Studies; Vol 38 No 6DO - 10.25073/2525-2445/vnufs.4887, 2022)
Genre is the linguistic level that is of interest to many researchers as evident in a large number of research papers related to genre analysis. In linguistics, genre analysis also has several directions of research with distinct techniques. In this paper, the theory of Generic Structure Potential, which was developed by Hasan Ruquaiya (1989), was used to investigate the macrostructure of legal discourse. The legal discourse chosen to examine was Vietnamese precedents. The method used in this article was the descriptive method through content analysis from the qualitative approach. The result of this study showed the macrostructure of Vietnamese precedents from the perspective of Generic Structure Potential. The article contributed to the picture of genre analysis with a variety of legal discourses. The description of the macrostructure helps to characterize the cultural context of Vietnamese precedent discourses that is considered as a stratum of discourse analysis from the perspective of Systemic Functional Linguistics.